The Influence of the Work Environment on Employee Performance with Work Discipline as a Mediating Variable (Study of Public Works and Spatial Planning Department Employees in Central Halmahera Regency) - Nurhalinda, Nurhalinda; Sabuhari, Rahmat; Kamis, Ruslan A (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to determine the effect of the work environment on performance which is mediated by work discipline in employees of the Department of Public Works and Spatial Planning in Central Halmahera Regency. This type of research is quantitative. The population in this study were 49 respondents, this study used a saturated sampling technique where all populations were sampled.  The analytical tool used is path analysis with the help of the SPSS 29 program. The results showed that the work environment has no significant effect on employee performance, the work environment has a positive and significant effect on work discipline, work discipline has a positive and significant effect on employee performance and  work discipline can mediate the influence of the work environment on employee performance.